Pengenalan Mobile Commerce Pada Anggota Koperasi Gentiaras Untuk Meningkatkan Penghasilan Rumah Tangga - Garaika; Fauzi; Muhamad Muslihudin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Digital-based sales technology or often known as electronic commerce has increased very rapidly as felt at the moment. With very fierce trade competition, the Gantiaras Cooperative in collaboration with two STMIK Pringsewu Higher Education Institutions, STIE Trisna Negara provides advisory services for home industry business owners who are members of the Bukaaras Cooperative to have a digital-based sales platform with the concept of mobile commerce. This Community Service activity aims to provide an understanding for the Members of the Cooperative Cooperative on how to market digital-based handicraft products, food, clothing, services and services. From this activity the members of the Gentiaras Cooperative who have a home industry business can market products quickly, precisely and safely so that customers can provide convenience for customers.